Financial efficiency estimation for a dental radiology laboratory - Marcu, Maria; Hedesiu, Mihaela; Bogdan, Loredana; Armencea, Gabriel; Manea, Avram; Roman, Raluca; Vacaras, Sergiu; Haba, Danisia; Porumb, Anca; Baciut, Mihaela; Crisan, Sorana (Medicine and Pharmacy Reports, 2020)
Background and aims. Considering nowadays trend among dentists to install a radiology laboratory beside their current practice, we proposed to investigate the aspect of financial efficiency related to such investment. Methods. We evaluate two existing options: simple investment, consisting of intra-oral equipment and accessories, or investment in a radiology center that includes panoramic and CBCT equipment. The initial investment includes equipment acquisition, fitting out of the location, radiology accreditation and other miscellaneous expenses. Costs were estimated based on current quotations on the specific market available in Romania. We also described a financial model to estimate the financial risk. Results. The analysis was made under the assumptions that the laboratory is operated by the dentist who made the investment in the form of a legal person and paying corporate tax like all Romanian entities. The analysis took into account current fees for different types of x-rays, usual expenses of such a laboratory, and describes the approach to this analysis, starting with the initial investment estimation and forecast of revenues and expenses. Based on these projections and assessment of the working capital, we have built the cash flows forecast. Following a risk analysis we could assess the financial efficiency of the two investment alternatives. Conclusions. Our study reveals that the radiology center represents a more profitable investment due to the higher economic return rate.